SOFTWARE REFACTORING COST ESTIMATION USING PARTICLE SWARM OPTIMIZATION - M. Sangeetha Dr. P. Sengottuvelan (International Journal of Research Science and Management, 2017)
“Now a day’s software industry major development cost devoted software maintenance. The major challenge for this industry is to produce quality software which is timely designed and build with proper cost estimates. Refactoring is used increasing the ability of software to adopt the new requirements and maintenance In this paper, we have proposed a cost estimation model based on Multi-objective Particle Swarm Optimization (MPSO) to tune the parameters of the famous Constructive Cost Model (COCOMO). This cost estimation model is integrated with Quality Function Deployment (QFD) methodology to support decision making in software designing and development processes for improving the quality. This approach helps to the developers to efficiently plan the overall software development life cycle.